Sukarno and Colonialism: An Analysis of Indonesia’s Foreign Policy Discourse, 1955-1961 - Ardhitya Eduard Yeremia (Jurnal Ilmiah Hubungan Internasional, 2020)
For the most part, the literature about Indonesia’s foreign policy does not stray far from a descriptive and chronological presentation of the subject. The fact of the matter is that an in-depth analysis of the nation’s foreign policy from a different era will impart valuable lessons to the current policymakers in charge of formulating and implementing such a policy. The era of Sukarno bore witness to the implementation of Indonesia’s foreign policy that was strong in ideas and practices. Employing discourse analysis, this article seeks to analyze five of Sukarno’s speeches, which were delivered in various international forums from 1955 to 1963. It demonstrates that during that time, Indonesia put forward a coherent and consistent foreign policy with colonialism as its master signifier. The promotion of such a discourse contributed positively to the diplomatic effort on the issue of West Papua by mobilizing supports from Asian-African nations, as well as attracting the interest of the superpowers. As a result, Indonesia’s national interest to bring West Papua into the Republic was well served, and furthermore, Indonesia succeeded in enhancing its image, role, and leadership in world affairs. This experience presents a challenge to the contemporary policymakers in producing a configuration of strong ideas and concepts that would allow the implementation of a foreign policy that serves the national interest, when the nation has once again risen as an important player on the world stage.